Hearing loss, hearing aid use, and performance on the Montreal cognitive assessment (MoCA): findings from the HUNT study in Norway - Moradi, Shahram; Engdahl, Bo; Johannessen, Aud; Selbæk, Geir; Aarhus, Lisa; Haanes, Gro Gade (Frontiers in Neuroscience, 2024)
Purpose To evaluate the associations between hearing status and hearing aid use and performance on the Montreal Cognitive Assessment (MoCA) in older adults in a cross-sectional study in Norway. Methods This study utilized data from the fourth wave of the Trøndelag Health Study (HUNT4, 2017–2019). Hearing thresholds at frequencies of 0.5, 1, 2, and 4 kHz (or PTA4) in the better hearing ear were used to determine participants’ hearing status [normal hearing (PTA4 hearing threshold, ≤ 15 dB), or slight (PTA4, 16–25 dB), mild (PTA4, 26–40 dB), moderate (PTA4, 41–55 dB), or severe (PTA4, ≥ 56 dB) hearing loss]. Both standard scoring and alternate MoCA scoring for people with hearing loss (deleting MoCA items that rely on auditory function) were used in data analysis. The analysis was adjusted for the confounders age, sex, education, and health covariates. Results The pattern of results for the alternate scoring was similar to that for standard scoring. Compared with the normal-hearing group, only individuals with moderate or severe hearing loss performed worse in the MoCA. In addition, people with slight hearing loss performed better in the MoCA than those with moderate or severe hearing loss. Within the hearing loss group, hearing aid use was associated with better performance in the MoCA. No interaction was observed between hearing aid use and participants’ hearing status with performance on the MoCA test. Conclusion While hearing loss was associated with poorer performance in the MoCA, hearing aid use was found to be associated with better performance in the MoCA. Future randomized control trials are needed to further examine the efficacy of hearing aid use on the MoCA performance. When compared with standard scoring, the alternate MoCA scoring had no effect on the pattern of results.